Stormen på Kongressen: Statskup, kitsch og billedbegivenhed - Bolt, Mikkel (K&K - Kultur og Klasse, 2022)
On 6 January 2021 far-right protesters stormed the Capitol in Washington DC, seat of the US Congress. The protesters were a mixed bag, some wore bulletproof vests, helmets and rifles, other came clad in Braveheart clothes, some were waving Confederate flags, some explicitly fascist ones. Once inside the building many protesters walked around taking selfies and stealing stuff from the offices of the Congress members who were hiding in the basement of the building. Other protesters sought to find specific members of Congress, including Nancy Pelosi, and Vice-President Mike Pence in order to hang them. The whole scene was chaotic, at once frightening and comic. The article proposes an analysis of the event as an instance of image politics using concepts and insights from Guy Debord and Walter Benjamin.